2005
DOI: 10.1063/1.2061527
|View full text |Cite
|
Sign up to set email alerts
|

Runaway electrons in a fully and partially ionized nonideal plasma

Abstract: This paper reports on a study of electron runaway for a nonideal plasma in an external electric field. Based on pseudopotential models of nonideal fully and partially ionized plasmas, the friction force was derived as a function of electron velocities. Dependences of the electron free path on plasma density and nonideality parameters were obtained. The impact of the relative number of runaway electrons on their velocity and temperature was considered for classical and semiclassical models of a nonideal plasma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
31
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…The atomic collision and radiation processes have been actively investigated by using the effective potentials based on the Yukawa-type Debye-Hückel model [6,19] and the ion-sphere model [20], respectively, in weakly coupled and strongly coupled plasmas. Recent years, the physical characteristics and properties of dense plasmas have been of great interests since the dense non-ideal plasma can be found in various astrophysical and laboratory environments such as astrophysical compact objects, intense laser-plasma experiments, nano-wires, quantum dots, and semiconductor devices [21][22][23][24][25][26][27][28]. In non-ideal plasmas [21][22][23], however, it is shown that the effective interaction potential and the electron pair-correlation function would not be properly represented by the Debye-Hückel theory owing to the influence of quantum and collective correlation effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The atomic collision and radiation processes have been actively investigated by using the effective potentials based on the Yukawa-type Debye-Hückel model [6,19] and the ion-sphere model [20], respectively, in weakly coupled and strongly coupled plasmas. Recent years, the physical characteristics and properties of dense plasmas have been of great interests since the dense non-ideal plasma can be found in various astrophysical and laboratory environments such as astrophysical compact objects, intense laser-plasma experiments, nano-wires, quantum dots, and semiconductor devices [21][22][23][24][25][26][27][28]. In non-ideal plasmas [21][22][23], however, it is shown that the effective interaction potential and the electron pair-correlation function would not be properly represented by the Debye-Hückel theory owing to the influence of quantum and collective correlation effects.…”
mentioning
confidence: 99%
“…Recent years, the physical characteristics and properties of dense plasmas have been of great interests since the dense non-ideal plasma can be found in various astrophysical and laboratory environments such as astrophysical compact objects, intense laser-plasma experiments, nano-wires, quantum dots, and semiconductor devices [21][22][23][24][25][26][27][28]. In non-ideal plasmas [21][22][23], however, it is shown that the effective interaction potential and the electron pair-correlation function would not be properly represented by the Debye-Hückel theory owing to the influence of quantum and collective correlation effects. Hence, it is expected that the occurrence times for the elastic electron-ion collision in non-ideal plasmas can be quite different from those in weakly coupled plasmas due to the quantum diffraction [28] and plasma screening effects.…”
mentioning
confidence: 99%
“…It is also shown that the entanglement fidelity in the collision process has received a considerable attention since it has been shown that the quantum correlation phenomenon [6] plays an important role for understanding the quantum measurements and information processing in various quantum systems. Recently, the physical properties of strongly coupled plasmas have been extensively investigated since the interiors of astrophysical compact objects and inertial confinement fusion plasmas would be classified as strongly coupled plasmas [7 -11].…”
mentioning
confidence: 99%
“…In addition, it has been shown that the interaction potential in strongly coupled semiclassical plasmas would not be represented by the conventional DebyeHückel model because of nonideal particle interactions due to collective and quantum effects. [10][11][12][13] However, the behavior of the Wannier threshold law for the double-electron escape in strongly coupled semiclassical plasmas has not been specifically investigated as yet. Thus, in this brief communication we investigate the quantum and plasma screening effects on the Wannier threshold law for the double-electron escape from the ion in strongly coupled semiclassical plasmas.…”
mentioning
confidence: 99%